The Effect of General Anesthesia vs. Regional Anesthesia on Postoperative Delirium—A Systematic Review and Meta-Analysis - Zhu, Xianlin; Yang, Min; Mu, Junying; Wang, Zaiping; Zhang, Liang; Wang, Hongbai; Yan, Fuxia (Frontiers in Medicine, 2022)
Background Postoperative delirium (POD) commonly occurs in patients following major surgeries and is associated with adverse prognosis. The modes of anesthesia may be associated with POD occurrence. General anesthesia (GA) causes loss of consciousness in the patient by altering the levels of some neurotransmitters as well as signaling pathways. We conducted this meta-analysis to investigate the effect of GA vs. regional anesthesia (RA) on POD incidence in surgical patients. Methods The databases of Pubmed, Embase, and Cochrane Library were searched till October 22, 2021. The eligible criteria were participants aged 18 years or older, patients undergoing surgery under GA and RA, and articles reporting the effect of GA vs. RA on POD incidence. RevMan 5.3 was used to perform statistical analyses. Results A total of 21 relevant trials with a total of 1,702,151 patients were included. The pooled result using random-effects model with OR demonstrated significant difference in POD incidence between patients with GA and RA (OR = 1.15, 95% CI: [1.02, 1.31], I2 = 83%, p for effect = 0.02). We did not obtain the consistent pooled result after sensitivity analysis (OR = 0.95, 95% CI: [0.83, 1.08], I2 =13%, p for effect = 0.44) and excluded the articles without the information on preoperative cognitive or neuropsychological assessment (OR = 1.12, 95% CI: [1.00, 1.25], I2 =80%, p for effect = 0.05), respectively. Conclusion This meta-analysis could not identify that GA was significantly associated with POD occurrence in surgical patients compared with RA.